The influence of gadgets on language development in early childhood - Wardani, Umi Sismia; Ashadi, Ashadi; Triyono, Sulis; Widodo, Pratomo; Andriyanti, Erna (Universitas Islam Sultan Agung, 2025)
This study aims to explore the effect of gadgets on language development in early childhood, specifically focusing on three-year-old participants. The digital era, characterized by rapid technological advancement, has significantly influenced daily life, posing challenges for parents as minors can easily gadgets without supervision. The study used qualitative research. The research method employed a case study that involved detailed observation. The data collection is about a single subject or small group, including direct observation of children and interviews with their parents. The CoComelon channel on YouTube was used as a medium for language development in this study. The findings of this research show that gadgets influence the development of language. Participants in this study demonstrated positive impacts, contrasting with the predominantly negative cases observed in Indonesia. The participants in this research are included in the stages of prelinguistic so that the children can get a verb from a show, and it is said repeatedly because the parents have rules for children to discipline based on the theory Piaget as quoted by Gin.